1975
DOI: 10.1159/000197723
|View full text |Cite
|
Sign up to set email alerts
|

Specific Lymphocyte Sensitization in Chronic Pancreatitis

Abstract: Specific lymphocyte sensitization was found in vitro using a lymphocyte transformation test with human pancreatic antigens. It should be possible to develop an immunological diagnostic test for chronic pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

1980
1980
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 1 publication
0
7
0
1
Order By: Relevance
“…Murray and Thal [1] and Fonkalsrud and Longemire [2] have found autoantibodies in patients with chronic pancreatitis. Schütt et al [3] demonstrated autoreactive peripheral blood lymphocytes. Bedossa et al [4], Jalleh et al 1 Leukocytes in Pancreatic Tissue Digestion 1998;59:192-198 193 [5], and our group [6] detected aberrant HLA-DR expression in pancreatic tissue of chronic pancreatitis patients.…”
Section: Introductionmentioning
confidence: 99%
“…Murray and Thal [1] and Fonkalsrud and Longemire [2] have found autoantibodies in patients with chronic pancreatitis. Schütt et al [3] demonstrated autoreactive peripheral blood lymphocytes. Bedossa et al [4], Jalleh et al 1 Leukocytes in Pancreatic Tissue Digestion 1998;59:192-198 193 [5], and our group [6] detected aberrant HLA-DR expression in pancreatic tissue of chronic pancreatitis patients.…”
Section: Introductionmentioning
confidence: 99%
“…Au toimmune mechanisms may contribute to the pathogene sis of chronic pancreatitis [16][17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…It was also reported that lymphocytes were sensitized specifically with the organ-specific human pancreatic antigens in most cases of chronic pancreatitis in man (16,17,21), and that antinuclear factors were detected in the serum of most patients with acute and chronic pancreatitis of unknown etiology (13). These results suggest that immunological mechanisms are involved in the development of some types of chronic pancreatitis in man.…”
mentioning
confidence: 99%